Vacuum-deposited donors for low-voltage-loss nonfullerene organic solar cells - Kaienburg, P; Bristow, H; Jungbluth, A; Habib, I; McCulloch, I; Beljonne, D; Riede, M (American Chemical Society, 2023)
The advent of nonfullerene acceptors (NFAs) enabled records of organic photovoltaics (OPVs) exceeding 19% power conversion efficiency in the laboratory. However, high-efficiency NFAs have so far only been realized in solution-processed blends. Due to its proven track record in upscaled industrial production, vacuum thermal evaporation (VTE) is of prime interest for real-world OPV commercialization. Here, we combine the benchmark solution-processed NFA Y6 with three different evaporated donors in a bilayer (planar heterojunction) architecture. We find that voltage losses decrease by hundreds of millivolts when VTE donors are paired with the NFA instead of the fullerene C60, the current standard acceptor in VTE OPVs. By showing that evaporated small-molecule donors behave much like solution-processed donor polymers in terms of voltage loss when combined with NFAs, we highlight the immense potential for evaporable NFAs and the urgent need to direct synthesis efforts toward making smaller, evaporable compounds.